Digital Nudge and UX Psychology: Improving Human Visual Perception on Mobile Platforms - Bae, Yebin; Im, Youngjae (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
This study aims to enhance mobile usability by applying nudge and Gestalt theories in UX psychology. As usability on mobile platforms significantly influences user experiences, the ergonomic design of visual elements has gained more importance. The recent UX trend emphasizes accessibility, efficiency, and personalization for optimal user experiences. Using Figma as an interface design tool, 10 mobile prototypes, such as food delivery and scheduling platforms, were tested by 18 participants. Usability was evaluated through performance time, number of clicks, and heatmaps. Applying digital nudges (defaults, reminders) and Gestalt principles (simplicity, proximity) improved human visual perception. Results showed a 63% reduction in performance time and 66% fewer clicks. Heatmaps confirmed better intuitiveness, and post-interviews highlighted increased satisfaction with the revised design. The findings emphasize the importance of tailored designs while validating the universal benefits of UX psychology.